Chronic urticaria and the metabolic syndrome: a cross‐sectional community‐based study of 11 261 patients. (14th September 2017) - Shalom, G.; Magen, E.; Babaev, M.; Tiosano, S.; Vardy, D.A.; Linder, D.; Horev, A.; Saadia, A.; Comaneshter, D.; Agmon‐Levin, N.; Cohen, A.D.
Abstract: Background: Emerging evidence suggests that chronic urticaria (CU) is associated with chronic, low‐grade, inflammatory process. Objective: To evaluate the association between CU and metabolic syndrome and its components in a large community‐based medical database. Methods: A cross‐sectional study of CU patients and matched controls was performed. CU was defined as eight urticaria diagnoses (with each two diagnoses registered within a period of 6 weeks) from 2002 to 2012. Data regarding the prevalence of metabolic syndrome, its components and possible complications were collected. Results: The study included 11 261 patients with CU and 67 216 controls. In a univariate analysis, CU was significantly associated with higher body mass index (BMI) and a higher prevalence of obesity, diabetes, hyperlipidaemia, hypertension, metabolic syndrome, chronic renal failure and gout. Multivariate analysis demonstrated a significant association between CU and metabolic syndrome (OR = 1.12, 95% CI 1.1–1.2, P < 0.001) and its components – obesity (OR = 1.2, 95% CI 1.1–1.3, P < 0.001), diabetes (OR = 1.08, 95% CI 1.01–1.15, P = 0.001), hyperlipidaemia (OR = 1.2, 95% CI 1.1–1.2, P < 0.001) and hypertension (OR = 1.1, 95% CI 1.1–1.2, P < 0.001). Conclusions: CU patients may have one or more undiagnosed components of metabolic syndrome despite their young age. Thus, appropriate targeted screening is advised.